2022
DOI: 10.1007/s00127-022-02333-8
|View full text |Cite|
|
Sign up to set email alerts
|

Mental health of young informal carers: a systematic review

Abstract: Purpose This systematic review aims to assess and evaluate quantitative evidence on the association between informal caregiving and mental health in young people. Methods This review was registered in PROSPERO (CRD42021251666). We conducted our search in the following four databases: Medline (PubMed and OVID), EMBASE, PsycInfo and Web of Science. The last search was performed on the 17th of March of 2021. Quantitative studies that focused on carers aged 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
(192 reference statements)
1
15
0
Order By: Relevance
“…In the context of recent systematic reviews on the mental health of young carers 10 , 30 , this paper directly answers the need for more causally focused research on this association, a key gap in this area 10 , 30 . Our results align with cross-sectional research demonstrating a negative association between young caring and mental health, with a clear dose–response relationship 31 , as well as other emerging longitudinal evidence supporting a causal effect of informal care on young people's mental health 11 , 13 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In the context of recent systematic reviews on the mental health of young carers 10 , 30 , this paper directly answers the need for more causally focused research on this association, a key gap in this area 10 , 30 . Our results align with cross-sectional research demonstrating a negative association between young caring and mental health, with a clear dose–response relationship 31 , as well as other emerging longitudinal evidence supporting a causal effect of informal care on young people's mental health 11 , 13 .…”
Section: Discussionmentioning
confidence: 76%
“…As mentioned in both systematic reviews, pathways through which young informal care leads to poor mental health outcomes have not been investigated 10 , 30 . Although recent evidence postulates benefit finding (the ability to identify positive changes after experiencing adverse events) as a protective factor for the mental health of young caregivers 34 , no previous study has explored the underlying mechanisms explaining the poorer psychological health of adolescent carers compared to their non-caring peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…National and international studies have found a lower quality of life and less social participation among YCs compared to their non-caregiving peers [ 1 , 3 ]. Many YCs remain invisible and without support [ 4 , 5 , 6 ], and they experience short- and longer-term risks in various areas of life, such as disadvantages for their own health and psychosocial well-being [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Youth who take on responsibilities related to caring for a family member with disability, serious physical or mental illness, or alcohol/substance use problems, or who provide assistance to elderly relatives who have lost their autonomy due to age are broadly referred to as young carers [ 1 , 2 ]. Evidence indicates that, compared to their non-caring peers, these youth are at elevated risk for poorer mental health as well as other adverse psychosocial outcomes, such as poorer education, economic hardship, and worse health, especially when they care for an ill parent [ 3 , 4 , 5 , 6 ]. While many of these studies have examined children and adolescent carers up to 18 years, carers in the emerging adult developmental stage (age 18–25), referred to as ‘young adult carers’, have received remarkably less research attention [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%